The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1109/tuffc.956
|View full text |Cite
|
Sign up to set email alerts
|

Theory and operation of 2-D array piezoelectric micromachined ultrasound transducers

Abstract: Piezoelectric micromachined ultrasound transducers (pMUTs) are a new approach for the construction of 2-D arrays for forward-looking 3-D intravascular (IVUS) and intracardiac (ICE) imaging. Two-dimensional pMUT test arrays containing 25 elements (5 x 5 arrays) were bulk micromachined in silicon substrates. The devices consisted of lead zirconate titanate (PZT) thin film membranes formed by deep reactive ion etching of the silicon substrate. Element widths ranged from 50 to 200 microm with pitch from 100 to 300… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(53 citation statements)
references
References 12 publications
0
50
0
Order By: Relevance
“…Despite achievements in pMUT research [1], [3], [4], [12]- [18], predictive modeling and optimization capabilities are limited in improving reduced effective electromechanical coupling k 2 ef f and bandwidth in fabricated devices. In the most mature recent projects, fabricated pMUT designs are based heavily on geometry specific finite element models [19] with analytical models commonly limited to resonant frequency determination [4], [16], [20], [21]. A lack of available models leading to performance shortcomings demonstrate a need for more robust, fundamental understanding of pMUT performance.…”
Section: Introductionmentioning
confidence: 99%
“…Despite achievements in pMUT research [1], [3], [4], [12]- [18], predictive modeling and optimization capabilities are limited in improving reduced effective electromechanical coupling k 2 ef f and bandwidth in fabricated devices. In the most mature recent projects, fabricated pMUT designs are based heavily on geometry specific finite element models [19] with analytical models commonly limited to resonant frequency determination [4], [16], [20], [21]. A lack of available models leading to performance shortcomings demonstrate a need for more robust, fundamental understanding of pMUT performance.…”
Section: Introductionmentioning
confidence: 99%
“…The piezoelectric micromachined ultrasonic transducers (PMUTs) also emerge as another possible 2D transducer solution for 3D imaging [47][48][49][50][51]. It combines the piezoelectric material with micromachining techniques, trying to exploit the benefits from both worlds.…”
Section: Ultrasonic Transducersmentioning
confidence: 99%
“…The piezoelectric material tends to provide transduction with relatively high efficiency and good linearity, while the micromachining process helps 35 create fine-pitched 2D arrays with higher yield and reliability. As a technology in its early research phase, it has shown initial success of a 5x5 working array [47]. More works are being done to address problems with this technology, including how to enhance the device bandwidth to generate images with better axial resolution; and how to reduce the intrinsic device parasitic capacitance from the high permittivity of the piezoelectric material [48,49,51].…”
Section: Ultrasonic Transducersmentioning
confidence: 99%
“…As a important functional materials, Pb(Zr 0.48 Ti 0.52 )O 3 (PZT) films have been widely used in micro acoustic sensor, non-volatile memory, uncooled infrared detectors for their excellent ferroelectric, piezoelectric, pyroelectric properties [1][2][3][4]. The study has shown that the properties of PZT films depend greatly on their orientation.…”
Section: Introductionmentioning
confidence: 99%